Effects of Window Films in Thermo-Solar Properties of Office Buildings in Hot-Arid Climates - Sedaghat, Ahmad; Abbas Oloomi, Seyed Amir; Malayer, Mahdi Ashtian; Alkhatib, Fadi; Sabri, Farhad; Sabati, Mohammad; Salem, Hayder; Zafar, Waqar Jan; Mostafaeipour, Ali; Issakhov, Alibek; Jahangiri, Mehdi; Techato, Kuaanan; et al. (Frontiers in Energy Research, 2021)
The electricity consumption in residential/office buildings reported 45% of the total annual electricity demand in hot-arid climates. This accounted 27.2 TWh of electricity consumption with 14.2 MWh/capita/year in Kuwait. In this research, four offices in an educational building are equipped with a meteorological data logging system using temperature, humidity and illuminance sensors. All four offices use double-glazed windows. Moreover, two offices were equipped with two types of commercially available window films. Two million data was stored in iCloud using WiFi and an IoT system for the three months of June, July, and August 2019. Here, histograms and the kernel density estimation (KDE) of temperature/humidity are analyzed and compared for the two offices with/without 3M Neutral 20 window films. Two floors of the same building consist of 31 offices were also modelled and simulated to study energy saving and CO2 footprint reduction using various window films. It is observed that annual energy saving and CO2 footprint reduction of 2.76% can be achieved using window films in a hot-arid climate.